Tobacco smoking in schizophrenia: investigating the role of incentive salience. Issue 10 (July 2014) - Freeman, T. P.; Stone, J. M.; Orgaz, B.; Noronha, L. A.; Minchin, S. L.; Curran, H. V.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Smoking is highly prevalent in people diagnosed with schizophrenia, but the reason for this co-morbidity is currently unclear. One possible explanation is that a common abnormality underpins the development of psychosis and independently enhances the incentive motivational properties of drugs and their associated cues. This study aimed to investigate whether incentive salience attribution towards smoking cues, as assessed by attentional bias, is heightened in schizophrenia and associated with delusions and hallucinations. Method Twenty-two smokers diagnosed with schizophrenia and 23 control smokers were assessed for smoking-related attentional bias using a modified Stroop task. Craving, nicotine dependence, smoking behaviour and positive and negative symptoms of schizophrenia were also recorded. Results Both groups showed similar craving scores and smoking behaviour according to self-report and expired carbon monoxide (CO), although the patient group had higher nicotine dependence scores. Attentional bias, as evidenced by significant interference from smoking-related words on the modified Stroop task, was similar in both groups and correlated with CO levels. Attentional bias was positively related to severity of delusions but not hallucinations or other symptoms in the schizophrenia group. Conclusions This study supports the hypothesis that the development of delusions and the incentive motivational aspects of smoking may share a common biological substrate. These findings may offer some explanation for the elevated rates of smoking and other drug use in people with psychotic illness.